Test-retest reliability evaluation of the Escala de Conciencia Cultural para Estudiantes de Terapia Ocupacional en América Latina (ECCETO) – Cultural Awareness Scale for Occupational Therapy Students in Latin America/Avaliação da confiabilidade teste - Castro, Daniela; Mårtensson, Lena; Dahlin-Ivanoff, Synneve (Cadernos Brasileiros de Terapia Ocupacional, 2017)
Introduction: Cultural awareness is an important consideration in healthcare, particularly in occupational therapy. Personal values are often challenged in service provision. Culturally relevant scales are needed to evaluate this across the professional education. Evaluation of psychometric properties is a critical issue in scale development. The test – retest reliability of the Escala de Conciencia Cultural para Estudiantes de Terapia Ocupacional en América Latina (ECCETO), (Cultural Awareness Scale for Occupational Therapy students in Latin America) has not yet been evaluated. Objective: To evaluate the test-retest reliability of the ECCETO. Method: The Svensson’s method was used to evaluate the ECCETO responses of 10 newly graduated Chilean occupational therapists and 26 occupational therapy students from four Latin American countries. Results: The scale had test-retest reliability, based on a reduced number of items presenting systematic disagreement, and showed good internal consistency. Conclusion: There were differences in the scale’s categories and between the study phases. Using the scale in larger groups of students may support reflective opportunities that promote early development of cultural awareness. Cultural awareness should be included in occupational therapy education in Latin America and worldwide. Adaptations of the ECCETO, should carefully consider the local practice context to preserve the cultural relevance in different regions.